Implementasi Konsep Quality Function Deployment (QFD) untuk Meningkatkan Kualitas Produk Usaha Bakery - Muhammad Sri Sadono; Guntarti Tatik Mulyati; Wahyu Purwanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2000)
Product development and design have in the past often concentrated on specification and performance required. With and abundance of production capacity from other companies, the customer has greatest freedom of choice and will increasingly exercise that freedom. Products that only just satisfy the basic needs of performance and specification, but miss out on additional desirable or 'excitment' features seen elsewhere, will probably cause the intending purchaser to select the competitor's product. Quality Function Deployment (QFD) is a powerful technique, which enables companies to anticipate and prioritize customer needs in their totality and to incorporate them effectively into the product and service provided for the end user. Quality Function Deployment is a process which brings together the lifecycle of a product from its conception. through design, manufacture, distribution, and use, until the product has, the costumer's opinion, served its expected life. The management of QFD ensures that vital consumer satisfaction and excitement attributes are recognized and developed, so that the company can achieve a competitive edge. It is equally, if not more, important that this is achieved profitability, thereby providing increased security of the business and for its emlpoyees. According to the result of research at bread customer, pronounced 9 primary customer requirements its separated at 26 secondary customer requirements. That customer requirements must be answer by company with 26 technical requirements has implementation step priority stage, which can give guidance to the companies management of QFD team for implementing the Total QUality Management concept.